The influence of perceived organizational support (POS) and psychological capital on organizational citizenship behavior (OCB) - Tri Oktianti Indrawiani; Ade Irma Anggraeni; Adi Indrayanto (Faculty of Economics and Business, Jenderal Soedirman University, 2018)
The purpose of this research is to analyze and to know the influence of perceived organizational support (POS) and psychological capital toward organizational citizenship behavior (OCB) in the context of semi-military based public organization of Civil Service Police Unit (Satpol-PP) of Banyumas Regency. The results of this study are expected to provide recommendations on important elements in the management of human resources in the context of public organizations, especially regarding organizational support and psychological capital. Quantitative approach was used in this research. Respondents were numbered 136 employees of the total population of 206 employees of Satpol-PP of Banyumas Regency. Method of probability sampling with simple random sampling technique was used in sampling method in this research. Testing of the relationship between variables used simple linear regression analysis method. The results showed that perceived organizational support is positively and significantly related to OCB and psychological capital is positively related to OCB. This provides input for semi-military based organizations to improve employee welfare and development as well as increase their psychological capital to increase employee's extra role behavior, thereby increasing organizational productivity.